Satisfaction with health care services of out patient department at Chitwan Medical College Teaching Hospital, Nepal - Rajbanshi, L; Dungana, GP; Gurung, YK; Koirala, D (Journal of Chitwan Medical College, 2014)
Patient satisfaction is one of the most desired outcomes of health care and it is directly related with effective utilization of health service. The objective of the study was to find out the outpatients’ satisfaction with health care services provided in the hospital. The cross sectional study was conducted on April 2013. Through stratified systematic random sampling technique, 776 patients were selected and interviewed at exit point using semi structure interview schedule. Out of the total patients, 63.9% were female and 36.1% were male. Majorities (45.5%) of them were of age group 20 to 39 years, 79.3% were married, and 15.2% were illiterate. Overall satisfaction level was 75.9% with mean score was 24.19 ± 2.92. Level of satisfaction was high: 764(98.5%) with access to care, 710(91.5%) with quality of care and 437(56.3%) with physical facility but low in 476(61.3%) with cost of healthcare and 394(50.8%) with courtesy of healthcare provider. Satisfaction level was significantly associated with availability of drugs and services in the hospital. It also had significant association with waiting time for showing report to doctor. Time taken for registration, consultation and investigations were not significantly associated with age, educational level, and socioeconomic status of the patients. Similarly sex, occupation and income of the patients had insignificant effect on the satisfaction. Thus, to make the service more responsive to the patient, the hospital management needs to improve the staff behavior, adequate supply of drugs and focus on reducing the waiting time. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10841 Journal of Chitwan Medical College 2014; 4(1): 11-18